2012
DOI: 10.1074/jbc.m111.279281
|View full text |Cite
|
Sign up to set email alerts
|

Relative Spatial Positions of Tryptophan and Cationic Residues in Helical Membrane-active Peptides Determine Their Cytotoxicity

Abstract: Background: Tryptophan side chains can influence the binding of amphipathic peptides to biological membranes. Results:The cytotoxic activity of model helical amphipathic peptides was markedly influenced by the positions of tryptophan residues in the sequence. Conclusion: Tryptophan residues located adjacent to a hydrophobic helical portion created the most potent cytotoxic peptides. Significance: More potent anticancer helical peptides can now be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…It was found that a Val to Lys substitution in the center of the non-polar face of a 26-residue amphipathic α-helical AMP effectively reduced the overall hydrophobicity by disrupting the continuous hydrophobic surface into 2 regions and decreased peptide self-association in aqueous solution to permit a higher degree of association with the prokaryotic cell membranes. Other studies have also found that the appropriate positioning of Trp residue(s) at the hydrophobic-hydrophilic interface of the helical wheel projection could provide an effective strategy to enhance helical stability and also increase the partitioning or penetration of designed AMPs into microbial membrane lipid bilayers with minimal effects on mammalian cell membranes or their mimics at concentrations required for antimicrobial activities [56,58,59]. Although α-helical AMPs represent the most widely investigated class of AMPs, other types of secondary structures such as β-sheets [43,60] and β-hairpin-like AMPs [61,62] have also been designed and evaluated.…”
Section: Structurementioning
confidence: 98%
“…It was found that a Val to Lys substitution in the center of the non-polar face of a 26-residue amphipathic α-helical AMP effectively reduced the overall hydrophobicity by disrupting the continuous hydrophobic surface into 2 regions and decreased peptide self-association in aqueous solution to permit a higher degree of association with the prokaryotic cell membranes. Other studies have also found that the appropriate positioning of Trp residue(s) at the hydrophobic-hydrophilic interface of the helical wheel projection could provide an effective strategy to enhance helical stability and also increase the partitioning or penetration of designed AMPs into microbial membrane lipid bilayers with minimal effects on mammalian cell membranes or their mimics at concentrations required for antimicrobial activities [56,58,59]. Although α-helical AMPs represent the most widely investigated class of AMPs, other types of secondary structures such as β-sheets [43,60] and β-hairpin-like AMPs [61,62] have also been designed and evaluated.…”
Section: Structurementioning
confidence: 98%
“…LUVs were prepared by the extrusion method as described previously (Rekdal et al 2012, Arias et al 2014a. Briefly, phospholipids dissolved in chloroform and methanol (2:1) were combined in a glass vial, dried under a gentle stream of nitrogen gas, and then placed under vacuum overnight to remove all trace of the organic solvents.…”
Section: Large Unilamellar Vesicles (Luvs) Preparationmentioning
confidence: 99%
“…For this, we used LUVs composed of POPC:POPS (2:1) and POPC, respectively, to represent the negatively charged surface of malignant cells and the neutrally charged surface of normal eukaryotic cells (Rekdal et al 2012). LFcinB1 and hLF11 alone did not induce any permeabilization of the POPC or POPC:POPS LUVs, whereas the peptide chimeras both resulted in higher levels of permeabilization for the POPC:POPS membranes (Fig.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different models describing the peptide-lipid interactions leading to membrane disruption by CAPs have been suggested [9][10][11][12][13][14][15], and the ability to adopt amphipathic structures with separated cationic (Lys and Arg residues) and hydrophobic regions (Val, Leu, Ile, Phe and Trp residues) has been established as important [16,17]. Furthermore, some of the CAPs demonstrate immunomodulatory activities such as chemo taxis and an induction of cytokine release (see [18] for a recent review).…”
mentioning
confidence: 99%